Coronary Artery Bypass Grafting Is Rarely Done in the Acute Care of ST-elevation Myocardial Infarction Patients Treated by Emergency Medical Services - Jake Toy; Caroline Lauer; Amy H. Kaji; Joseph L. Thomas; Nichelle Megowan; Nichole Bosson; Marianne Gausche-Hill; Puneet Dhawan; Robert A. Kloner; Sara Rasnake; William French; Shira Schlesinger (Western Journal of Emergency Medicine)
Introduction: The use of coronary artery bypass grafting (CABG) for primary revascularization during the acute care of ST-elevation myocardial infarction (STEMI) patients has declined significantly in the past decade; but there is little data to determine whether there has been a change in the use of CABG for STEMI patients treated by emergency medical services (EMS). In this study we described the incidence of urgent or emergent CABG for STEMI patients treated in a large, regionalized cardiac care system. Methods: We obtained data obtained for patients transported by EMS between January 2011–December 2022 who were diagnosed with acute STEMI on prehospital or emergency department (ED) electrocardiogram and taken for primary diagnostic catheterization. All STEMI patients were transported by EMS to one of 34 STEMI receiving centers (SRC) in a regionalized cardiac care system, all of which are required to maintain onsite cardiac surgery as a condition of their SRC designation. Patients were considered to have undergone urgent or emergent CABG if it was performed within 72 hours of the primary diagnostic cardiac catheterization. We excluded patients if no diagnostic catheterization was performed or if CABG was performed >72 hours after diagnostic catheterization. The primary outcome was the incidence of urgent or emergent CABG. Patients were further stratified by time between diagnostic catheterization and CABG (<24 hours, 24–48 hours, 48–72 hours). Results: A total of 28,349 patients were transported by EMS and diagnosed with an acute STEMI during the study period. Only 384 (1.35%) patients underwent CABG within 72 hours of diagnostic catheterization: 268 (0.95%) underwent CABG in <24 hours; 71 (0.25%) in 24–48 hours, and 45 (0.16%) in 48–72 hours. The median age of patients undergoing CABG was 64 years (interquartile range 58–72). Twenty-eight (7.3%) experienced prehospital cardiac arrest, and eight (2.1%) required vasopressors. Prior to undergoing CABG, 137 patients (36%) underwent primary percutaneous coronary intervention. The proportion of patients undergoing CABG within 72 hours remained relatively stable between 2011–2022 at 1.19% and 1.96%, respectively. Conclusion: Urgent or emergent CABG remained infrequently performed for acute STEMI patients after primary diagnostic catheterization. There was little change in the percentage of STEMI patients who received CABG within 72 hours of diagnostic catheterization over the past decade. These findings suggest that regional or local policies requiring on-site cardiac surgery at SRCs may be reconsidered.